Ferruginibacter albus sp. nov., isolated from a mountain soil, and Mucilaginibacter robiniae sp. nov., isolated from a black locust flower, Robinia pseudoacacia. Issue 9 (22nd September 2022) - Won, Miyoung; Weon, Hang-Yeon; Heo, Jun; Lee, Daseul; Han, Byeong-Hak; Hong, Seung-Beom; Kwon, Soon-Wo
Abstract : Two bacterial strains, designated KIS38-8 T and F39-2 T, were isolated from a mountain soil sample and a black locust flower ( Robinia pseudoacacia ) in Republic of Korea, respectively. The phylogenetic tree based on 16S rRNA gene sequences showed that strain KIS38-8 T was classified into the genus Ferruginibacter with the highest sequence similarity to Ferruginibacter lapsinanis HU1-HG42 T (96.6 %), and strain F39-2 T was grouped into the genus Mucilaginibacter with the highest sequence similarity to Mucilaginibacter daejeonensis Jip 10 T (97.6 %). Orthologous average nucleotide identity and digital DNA–DNA hybridization values between strain KIS38-8 T and closely related Ferruginibacter strains were less than 72 and 19 %, respectively, while those values between strain F39-2 T and closely related Mucilaginibacter strains were less than 73 and 21 %, respectively. The DNA G+C contents of strain KIS38-8 T and F39-2 T were 36.4 and 41.4 mol%, respectively. On the basis of the phenotypic and genotypic evidence, strains KIS38-8 T and F39-2 T are considered to represent novel species of the genus Ferruginibacter and Mucilaginibacter, respectively, for which the names Ferruginibacter albus sp. nov. (type strain KIS38-8 T =KACC 17328 T =NBRC 113101 T ) and Mucilaginibacter robiniae sp. nov. (type strain F39-2 T =KACC 19733 T =JCM 33062 T ) have been proposed.